Recognition, Prevention, and Management of Arrhythmias and Autonomic Disorders in Cardio-Oncology: A Scientific Statement From the American Heart Association. Issue 3 (20th July 2021) - Fradley, Michael G.; Beckie, Theresa M.; Brown, Sherry Ann; Cheng, Richard K.; Dent, Susan F.; Nohria, Anju; Patton, Kristen K.; Singh, Jagmeet P.; Olshansky, Brian
Abstract : With the advent of novel cancer therapeutics and improved screening, more patients are surviving a cancer diagnosis or living longer with advanced disease. Many of these treatments have associated cardiovascular toxicities that can manifest in both an acute and a delayed fashion. Arrhythmias are an increasingly identified complication with unique management challenges in the cancer population. The purpose of this scientific statement is to summarize the current state of knowledge regarding arrhythmia identification and treatment in patients with cancer. Atrial tachyarrhythmias, particularly atrial fibrillation, are most common, but ventricular arrhythmias, including those related to treatment-induced QT prolongation, and bradyarrhythmias can also occur. Despite increased recognition, dedicated prospective studies evaluating true incidence are lacking. Moreover, few studies have addressed appropriate prevention and treatment strategies. As such, this scientific statement serves to mobilize the cardio-oncology, electrophysiology, and oncology communities to develop clinical and scientific collaborations that will improve the care of patients with cancer who have arrhythmias. Abstract : Supplemental Digital Content is available in the text.